Determination of geometry of cutting tool for smallsize machining of parts made of titanium alloys - D. S. Rechenko; D. G. Balova; A. K. Aubakirova; R. U. Kamenov; D. E. Levin (Омский научный вестник)
Requirements for the quality of manufacturing implants made of titanium alloys used in medicine are quite high. At the same time existing processing methods in their manufacture do not always provide the required quality of the treated surfaces, characterized by roughness and surface layer defects of the final part. The article proposes the constructions of carbide tools of various geometric shapes allowing to obtain different quality processing parameters. The aim of the research is testing new constructions of carbide end tools allowing to obtain the required quality parameters of fasteners of the screw for osteosynthesis ensuring the minimum defective layer. To achieve this goal in the work of the problem are solved: the manufacture of end carbide cutting tools of various geometric shapes; testing of cutting tools at recommended cutting conditions; control of roughness of processed surface. The results of testing metal-cutting tools in the processing of titanium alloy brand VT1-00, which is relevant from the point of view of the use of a new carbide end tool.